ANALISIS PENGARUH FAKTOR LOKASI, INFRASTRUKTUR, LAYANAN DAN BIAYA TERHADAP KELANCARAN DISTRIBUSI BARANG DI KABUPATEN MIMIKA - Reni Anna Parubak; Yahya Nusa (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study aims to determine the factors that influence the smooth distribution of goods in Mimika Regency. This study uses an associative method of collecting questionnaire data sourced from distributors in Mimika Regency, with a sample size of 30 respondents. The data analysis technique uses multiple linear regression and SPSS version 29. The results show that the factors of location (X1), infrastructure (X2), and cost (X4) do not affect the smooth distribution of goods in Mimika Regency, while the service indicator (X3) does affect the smooth distribution of goods in Mimika Regency.